Routing in wireless ad hoc networks. (1st January 2012) - Rishiwal, Vinay; Yadav, Mano
A routing strategy that finds a path to be followed by packets from a source node to a destination node used in traditional wired networks cannot be directly applied in ad hoc wireless networks due to their highly dynamic topology, absence of established infrastructure for centralised administration, bandwidth constrained wireless links, and energy constrained nodes. This paper first presents the issues involved in designing a routing protocol and then the different classifications of routing protocols for ad hoc wireless networks. It then discusses the working of several existing routing protocols with their merit and demerits. This survey helps to decide the weaknesses, strength and applicability of an existing routing protocol in different network scenarios and paves the path to develop an efficient routing protocol to cope up with most of the existing problems related to routing in MANETs.